2010
DOI: 10.1007/s10517-010-1000-6
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Peptide Deltorphin II Simulates the Cardioprotective Effect of Ischemic Preconditioning: Role of δ2-Opioid Receptors, Protein Kinase C, and KATP Channels

Abstract: The cardioprotective properties of a δ₂-opioid receptor agonist deltorphin II were studied in rats with coronary occlusion and reperfusion. Opioid receptor ligands and inhibitors (glybenclamide, chelerythrine, and 5-hydroxydecanoate) were injected intravenously before ischemia and reperfusion. A δ₂-opioid receptor agonist deltorphin II significantly decreased the infarction zone/risk zone index. This effect was abolished by naltrexone, naloxone methiodide, and δ₂-opioid receptor antagonist naltriben, but not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Cell suspensions with more than 85% viability were plated and cultured for further experiments. The cells were grown uniformly and seeded in 25 cm 2 flasks at the density of 1x10 6 /l and then maintained in culture containing …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell suspensions with more than 85% viability were plated and cultured for further experiments. The cells were grown uniformly and seeded in 25 cm 2 flasks at the density of 1x10 6 /l and then maintained in culture containing …”
Section: Methodsmentioning
confidence: 99%
“…Studies have found that the agonist of the δ-opioid receptor stimulates the proliferation of neonatal rat cardiac myocytes (5) and mimics the protective effects of ischemic preconditioning on heart and brain tissue (6,7). These findings have demonstrated that the δ-opioid receptor plays a significant role in the growth and maintenance of cells.…”
Section: Introductionmentioning
confidence: 99%
“… ‡ [1] (van Rijn et al 2010), [2] (Saitoh et al 2005) [3], (Margolis et al 2008), [4] (Sugiyama et al 2012), [5] (Randall-Thompson et al 2010), [6] (Krishnan-Sarin et al 1995) [7] (van Rijn and Whistler 2009), [8] (Matsuzawa et al 1998), [9] (Bie et al 2009a), [10] (van Rijn et al 2012a), [11] (Kamei et al 1994b), [12] (Kamei et al 1993b), [13] (Kamei et al 1991), [14] (Tortella et al 1984), [15] (Tortella et al 1988), [16] (Saitoh et al 2011), [17] (Yajima et al 2000), [18] (Di Giannuario et al 2001), [19] (Capasso and Cavallo 2005), [20] (Mizoguchi et al 1996), [21] (Fraser et al 2000b), [22](Sharp et al 1998), [23] (Miyamoto et al 1994), [24] (Miyamoto et al 1993a), [25] (Miyamoto et al 1993b), [26] (Suzuki et al 1997), [27] (Broccardo and Improta 1992b), [28] (Broccardo and Improta 1992a), [29] (Krevsky et al 1991), [30] (Fox-Threlkeld et al 1994), [31] (Pairet and Ruckebusch 1984), [32] (Shook et al 1989), [33] (Torregrossa et al 2006), [34] (Charron et al 2008), [35] (Maslov et al 2010b), [36] (Maslov et al 2010a), [37] (Guo et al 2005), [38] (Yang et al 2011), [39] (Lasukova et al 2009), [40] (Stewart and Hammond 1994), [41] (Mika et al 2001), [42] (Taiwo and Levine 1991), [43] (Fraser et al 2000a), [44] (Hurley and Hammond 2000), [45] (Cahill et al 2003), [46] (Holdridge and Cahill 2007), [47] (Ukai et al 1997), [48] (Castellano and Pavone 1985) …”
Section: Figurementioning
confidence: 99%
“…However, it appears that DOR subtype selectivity plays less of an important role for some other potential DOR-mediated side effects. Many DOR1- and DOR2-subtype selective agonists (DPDPE (Charron et al 2008; Lasukova et al 2009; Yang et al 2011), SNC-121(Patel et al 2006), Eribis peptide 94(Karlsson et al 2011), fentanyl isothiocyanate[FIT] (Gross et al 2005), BW373U86 (Peart et al 2011), TAN-67 (Guo et al 2005), ARD-353 (Watson et al 2006), deltorphin II (Maslov et al 2010a) have cardioprotective abilities. While a study by Mslov et al suggested that only the DOR2 selective deltorphin II, but not DPDPE, reduced infarct size (Maslov et al 2010b), these differences may relate to experimental procedures (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that δ receptor activation may promote the proliferation of rat myocardial cells (8,9) and imitate ischemia preconditioning to protect the heart and brain (10,11). As studies of δ receptor functions have continued, it has been shown that the δ receptor is critical in the regulation of the onset and development of cardiac diseases.…”
Section: Introductionmentioning
confidence: 99%